2006
DOI: 10.1136/vr.159.17.552
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anti‐inflammatory effects of treating endotoxin‐challenged pigs with meloxicam

Abstract: The clinical and anti-inflammatory effects of a single treatment of 0.4 mg meloxicam/kg bodyweight on pigs that had been challenged with Escherichia coli endotoxin were investigated. Significantly lower total clinical scores were recorded in pigs treated with meloxicam than in pigs treated with a placebo. Significantly higher mean serum concentrations of thromboxane B(2) were also recorded in pigs treated with a placebo for up to 24 hours after the challenge. The serum concentrations of acute phase proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…(Klosterhalfen et al, 1992;Mustonen et al, 2012). However, Friton et al (2006) established a maximal TXB 2 concentration only at 2 h p.a. of LPS, while Peters et al (2012) detected no increase at all in pigs.…”
Section: Thromboxane B 2 and Pulmonary Hypertensionmentioning
confidence: 91%
See 2 more Smart Citations
“…(Klosterhalfen et al, 1992;Mustonen et al, 2012). However, Friton et al (2006) established a maximal TXB 2 concentration only at 2 h p.a. of LPS, while Peters et al (2012) detected no increase at all in pigs.…”
Section: Thromboxane B 2 and Pulmonary Hypertensionmentioning
confidence: 91%
“…(Johnson and von Borell, 1994). Pretreatment of pigs with meloxicam or flunixin meglumine significantly decreased the clinical symptoms induced by LPS-challenge, including lethargy, skin flushing, vomiting, coughing and labored breathing (Friton et al, 2006;Peters et al, 2012). Different oral doses of ketoprofen p.a.…”
Section: Effects On Clinical Symptoms and Febrile Responsementioning
confidence: 98%
See 1 more Smart Citation
“…Regarding NSAIDs, a study conducted in rats and mice found that the therapeutic index of meloxicam is higher than that of other NSAIDs, including piroxicam, diclofenac and indomethacin. Meloxicam, an NSAID of the oxicam class, acts by inhibiting prostaglandin synthesis (Engelhardt and Trummlitz, 1990) and inducible cyclo-oxygenase-2 (COX-2; Engelhardt, 1996), thereby exerting anti-inflammatory, antitoxic, antiexudative, analgesic and antipyretic effects (Friton et al, 2006). Meloxicam is used for noninfectious locomotor disorders in pigs, by reducing the signs of lameness and inflammation (Friton et al, 2003), the porcine respiratory disease complex in growing pigs (Georgoulakis et al, 2006) and for the relief of post-operative pain associated with minor soft tissue surgery such as castration (Keita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…for the pharmacokinetic and pharmacodynamic study of meloxicam in piglets. The same single dose of meloxicam in adult pigs was used by Swindle (2007) and Friton et al (2006) in endotoxemia therapy and by Hirsch et al (2003) in mastitis-metritis-agalactia syndrome therapy. A similar dosage (0.3 mg/kg) was administered by Girod et al (2000Girod et al ( , 2002 in their studies on the antiemetic effects of meloxicam.…”
Section: Discussionmentioning
confidence: 99%